The Role of Vocational Education in Addressing Labor Shortages in Aging China - Qianyan Wu (Law and Economy, 2024)
China’s rapidly aging population presents significant challenges to its labor market, with acute shortages threatening economic growth and industrial productivity. This paper explores the critical role of vocational education as a strategic solution to address these labor shortages. By equipping workers with industry-relevant skills, vocational education enhances workforce competitiveness, supports the reskilling of older workers, and reduces regional disparities in economic opportunities. The paper delves into the challenges facing vocational education, including societal perceptions, curriculum modernization, and regional access inequalities, while highlighting opportunities for systemic reform and collaboration with industry stakeholders. It argues that vocational education is not merely a response to immediate labor shortages but a cornerstone for China’s long-term economic transformation and sustainability. By embracing vocational education as a forward-looking strategy, China can mitigate the impacts of demographic shifts and build a resilient, inclusive, and future-ready economy.